1989
DOI: 10.1080/00223980.1989.10543004
|View full text |Cite
|
Sign up to set email alerts
|

Personality Profiles of Homosexual Men and Women

Abstract: There has been surprisingly little research on possible differences between homosexual and heterosexual personalities, although the few studies that have been conducted suggest some interesting differences. We devised two hypothesis that may account for these differences. First, differences appear to reflect generalized social nonconformity and alienation due to the social stigmatization of the homosexual. Second, these differences seem to express a more specific tendency to deviation from socially normative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In addition, the scale is relatively specific to sexual orientation, having few other behavioral correlates (Long & Graham, 1991). Although other personality scales have occasionally obtained differences between heterosexual and homosexual men (e.g., Duckitt & du Toit, 1989;Evans, 1970), these have been neither consistent nor of comparable magnitude to those obtained with the Mf Scale. Moreover, where more reliable differences have been found, they have been obtained with related measures, such as the California Psychological Inventory Femininity Scale (Green, 1987;Pillard, 1990).…”
Section: Evidence That Male Sexual Orientation Is a Matter Of Degree ...mentioning
confidence: 78%
“…In addition, the scale is relatively specific to sexual orientation, having few other behavioral correlates (Long & Graham, 1991). Although other personality scales have occasionally obtained differences between heterosexual and homosexual men (e.g., Duckitt & du Toit, 1989;Evans, 1970), these have been neither consistent nor of comparable magnitude to those obtained with the Mf Scale. Moreover, where more reliable differences have been found, they have been obtained with related measures, such as the California Psychological Inventory Femininity Scale (Green, 1987;Pillard, 1990).…”
Section: Evidence That Male Sexual Orientation Is a Matter Of Degree ...mentioning
confidence: 78%
“…Clinical reports of gay men and lesbians' experiences of their sexual education, both in the family and in the schools, have pointed out omissions that have contributed to feelings of alienation and confusion about sexuality and identity ( Duckitt & du Toit, 1989;Garnets & D 'Augelli, 1994;0 'Conor, 1993-94;&in-Williams, 1989). These examples articulate the distress that occurs in the clash between societal assumptions of heterosexuality and an individual or family's experience of homosexuality.…”
Section: Gender Culture and Mental Healthmentioning
confidence: 99%
“…Male homosexuals overwhelmingly tend to be less masculine, more tender-minded, and less dominant than heterosexual males. At the same time, however, homosexual males are more unconventional and less submissive to authority than heterosexual males (Duckitt and duToit, 1989). On the other hand, Hassell and Smith (1975) found that female homosexuals are more dominant, independent, and tough-minded than heterosexual females.…”
Section: Personality Traitsmentioning
confidence: 99%